2014
DOI: 10.1111/jocd.12079
|View full text |Cite
|
Sign up to set email alerts
|

Multiple fractional erbium: yttrium–aluminum–garnet laser sessions for upper facial rejuvenation: clinical and histological implications and expectations

Abstract: Multiple sessions are effective in rejuvenation of the aging face with high safety, short downtime, and no adverse effects. They stimulated formation of new collagen (type I, III, and VII) up to 6 months after treatment with better improvement in skin texture and fine wrinkles. The variable number of fractional Er:YAG laser sessions (3-5) showed no significant difference as regards efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
1
32
0
1
Order By: Relevance
“…Calabaro et al reported that the WSRS is a valid instrument with a good intra-and interobserver agreement, but no statistical analysis has been used in this study. Furthermore, the use of a scale or questionnaire to assess patient satisfaction is very important to determine patient aspect and satisfaction degree; patient satisfaction appears as an essential item but these subjective clinical assessments lack the precision of the quantitative methods [12,21,22,26,28,42,44,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calabaro et al reported that the WSRS is a valid instrument with a good intra-and interobserver agreement, but no statistical analysis has been used in this study. Furthermore, the use of a scale or questionnaire to assess patient satisfaction is very important to determine patient aspect and satisfaction degree; patient satisfaction appears as an essential item but these subjective clinical assessments lack the precision of the quantitative methods [12,21,22,26,28,42,44,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding objective methods, the histological examination is the gold standard [11,12,26,[29][30][31][32] but it cannot be used routinely because of its cumbersomeness and invasiveness. Thus, these invasive procedures are time and cost-consuming as well as raise ethical concerns producing scarring of the skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В результа-те лазерного воздействия укорачиваются межмо-лекулярные поперечные связи тройной спирали коллагена, что приводит к мгновенному сокраще-нию коллагеновых волокон, обработанная ткань при этом сжимается. Принято считать, что фото-термическая реконструкция тканей является глав-ным эффектом эрбиевого лазера [9,12]. В то же время работы, посвященные анализу механизмов структурной реорганизации тканей стенки влага-лища, индуцированных Er:YAG-лазером, все еще немногочисленны [2].…”
unclassified